2009
DOI: 10.1093/ndt/gfp268
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in proteoglycan components and histopathology of the peritoneum in uraemic and peritoneal dialysis (PD) patients

Abstract: It appears that alterations in PGs, including marked induction of versican with peritonitis and disappearance of decorin, are involved in peritoneal remodelling in PD patients. Versican expression was closely related to the appearance of myofibroblasts and macrophages. These observations suggest that the alteration in PG components following PD therapy and severe inflammation contribute to fibrous thickening of the peritoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
(19 reference statements)
1
28
0
Order By: Relevance
“…Macrophages are one of the main cell populations mediating inflammation, and play an important role in innate and adaptive immune responses (24,25). Osada et al proved that CD68-positive cells (macrophages) in the peritoneum were marked in long-term PD patient samples (26). Our study showed that macrophages were significantly increased in the peritoneum of rats administered daily i.p.…”
Section: Discussionsupporting
confidence: 49%
“…Macrophages are one of the main cell populations mediating inflammation, and play an important role in innate and adaptive immune responses (24,25). Osada et al proved that CD68-positive cells (macrophages) in the peritoneum were marked in long-term PD patient samples (26). Our study showed that macrophages were significantly increased in the peritoneum of rats administered daily i.p.…”
Section: Discussionsupporting
confidence: 49%
“…Since versican is a component of the tumor inflammatory response facilitating lung metastases (50) and has been linked to macrophage-mediated inflammatory vascular disease (9,10,12,14,29,38,(51)(52)(53)(54), we hypothesized that GDI2 might suppress lung metastasis through downregulation of versican, in turn leading to a reduction of macrophage lung infiltration. We compared macrophage infiltration within and adjacent to metastatic lung foci that developed after tail-vein injection of GFP and GDI2 cells and found a reduction in mice injected with GDI2 cells compared with GFP controls ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Giebel et al have reported that elevated MMP-2 or MMP-9 expression in the retina may facilitate an increase in vascular permeability by degrading occludin, the tight junction protein of endothelial or epithelial cells [32]. Osada the blood vessels in the peritoneal tissues from long-term PD patients [33]. In PD, destruction of the tight junction of endothelial cells by MMP-2 may result in hyperpermeability of the peritoneum.…”
Section: Mmps As Peritoneal Injury Markers In Clinical Diagnosismentioning
confidence: 99%
“…[44], which may explain why drainage levels of MMP-2 reflects the peritoneal transport ratio. Activated mesenchymal cells, such as myofibroblasts or fibroblasts, synthesize ECM proteins or migrate during the disassemble of ECM of the peritoneum by MMP-2 or other proteinases [8][9][10][11][12]33]. Presence of excessive ECM proteins, such as collagen, leads to peritoneal fibrosis with peritoneal thickening and promotes the production of MMP-2 by myofibroblasts [9].…”
Section: Production Of Mmp-2 In the Peritoneummentioning
confidence: 99%
See 1 more Smart Citation